Testicular microlithiasis in a boy with X-linked adrenal hypoplasia congenita - Serbis, Anastasios (Ann Pediatr Endocrinol Metab, 2018)
X-linked adrenal hypoplasia congenita (AHC) is a rare disorder that usually presents clinically as adrenal insufficiency in early infancy. It is caused by mutations in the NR0B1 gene which is located on the short arm of chromosome X (Xp21). The NR0B1 gene plays an important role in normal development and function of both the adrenal and gonadal axes and some patients with the disease can present in adolescence with hypogonadotropic hypogonadism. Testicular microlithiasis is an ultrasonographic finding of unknown etiology that has been associated with several benign conditions such as cryptorchidism, congenital adrenal hyperplasia, varicoceles, and testicular malignancy. We report the case of an 11-year-old boy who was diagnosed at the age of 8 months with X-linked AHC due to adrenal failure and presented testicular microlithiasis during follow-up. To the best of our knowledge, this is the first case of an X-linked AHC patient diagnosed with testicular microlithiasis in follow-up.